Examining Louisiana State University College of Agriculture Students’ Perceived Motivators and Barriers to Participation in International Experiences - J. C. Bunch; Joey J. Blackburn; Shelli DanJean; Kristin E. Stair; Leslie Blanchard (Journal of International Agricultural and Extension Education, 2015)
In an effort to internationalize higher education and produce globally competent professionals, many universities have increased the time and financial assets put toward promoting an international experience (IE). Research supports using an IE to supplement international education efforts and help students develop the global perspective and experience needed to succeed in the workplace. The purpose of this study was to determine College of Agriculture (CoA) students’ perceptions of IE participation, and identify factors that CoA students perceived as barriers and motivators to participation in an IE. CoA students were interested in an IE. Overall life experience was identified as the most agreed motivator, and financial cost was identified as the most agreed barrier. No differences were found in perceived motivators or barriers of CoA students based on academic status. University faculty should encourage students who have participated in an IE to provide presentations and workshops to other CoA students. Further, presentations should focus on overall life experiences students gained from their IE participation, and should be informal in nature to allow for peer-to-peer discussion. This study should be replicated at other peer and regional universities for comparison, and a longitudinal study could be conducted to identify trends over time. Differences in gender and major regarding barriers and motivators should also be examined.
Keywords: Motivations; Barriers; International Experiences; Undergraduate Education; College of Agriculture